(untitled) (Revista Internacional de Formação de Professores, 2017)
This article is a summary of the dissertation of Santos (2016) linked to the Center for Studies and Research on Narratives. Training and Teaching Work (Nepen ) developed at the Graduate Program in Education of the Federal University of São Carlos (UFSCAR) -Sorocaba campus. Is focused on perceptions about gender and sexuality to teachers who work in the Youth and Adult Education (EJA), with the following issues: What are the perceptions about gender and sexuality evidenced in educational narratives produced by teachers who work in adult education and from them which setting can guide their educational practices? To answer we defined the objectives : Understanding the perceptions of gender and sexuality to teachers who work in adult education and the importance of discussing these issues in the statement of respect for differences within the school. Point out problems for convergence between the act of educating and issues related to gender and sexuality in EJA. Discuss gender and sexuality issues in the relations of daily school EJA driving the reflection on the values that mark our society. It is structured from a qualitative perspective and uses for production data preparation of educational narratives in an extension course, considers for the analysis pre categories defined by Novoa (2009): practice, personagens, sharing and public. As a result envisions offering educational grants for improving the social quality of adult education.